THE METHOD OF ULTRASOUND DENSITOMETRY AT THE DIAGNOSTICS OF OSTEOPENIA IN THE PREGNANCY - Amro, I.G.; Grischenko, O.V.; Grischenko, M.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
96 pregnant women aged from 17-42 years were examined. Structural and functional state of the bonе tissue was evaluated using the method of ultrasound densitometry. The author has proved the necessity of earli diagnosis of osteopenia for reduction of risk to birth a childrens with fetal orthopedics defects, and prophilaxis of clinical forms of osteoporosis in postmenopausal period.